Identification and experimental validation of key extracellular proteins as potential targets in intervertebral disc degeneration - Guang-Zhi Zhang; Lei Li; Zhang-Bin Luo; Cang-Yu Zhang; Yong-Gang Wang; Xue-Wen Kang (Bone & Joint Research, 2023)
Aims: This study aimed, through bioinformatics analysis and in vitro experiment validation, to identify the key extracellular proteins of intervertebral disc degeneration (IDD). Methods: The gene expression profile of GSE23130 was downloaded from the Gene Expression Omnibus (GEO) database. Extracellular protein-differentially expressed genes (EP-DEGs) were screened by protein annotation databases, and we used Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) to analyze the functions and pathways of EP-DEGs. STRING and Cytoscape were used to construct protein-protein interaction (PPI) networks and identify hub EP-DEGs. NetworkAnalyst was used to analyze transcription factors (TFs) and microRNAs (miRNAs) that regulate hub EP-DEGs. A search of the Drug Signatures Database (DSigDB) for hub EP-DEGs revealed multiple drug molecules and drug-target interactions. Results: A total of 56 EP-DEGs were identified in the differential expression analysis. EP-DEGs were enriched in the extracellular structure organization, ageing, collagen-activated signalling pathway, PI3K-Akt signalling pathway, and AGE-RAGE signalling pathway. PPI network analysis showed that the top ten hub EP-DEGs are closely related to IDD. Correlation analysis also demonstrated a significant correlation between the ten hub EP-DEGs (p＜0.05), which were selected to construct TF–gene interaction and TF–miRNA coregulatory networks. In addition, ten candidate drugs were screened for the treatment of IDD. Conclusion: The findings clarify the roles of extracellular proteins in IDD and highlight their potential as promising novel therapeutic targets. Cite this article: Bone Joint Res 2023;12(9):522–535.